Iridium Azocarboxamide Complexes: Variable Coordination Modes, C-H Activation, Transfer Hydrogenation Catalysis, and Mechanistic Insights - Chandra, Shubhadeep; Kelm, Ola; Albold, Uta; Hazari, Arijit Singha; Urankar, Damijana; Kosmrlj, Janez; Sarkar, Biprajit (Organometallics, 2021)
Azocarboxamides, a special class of azo ligands, display intriguing electronic properties due to their versatile binding modes and coordination flexibility. These properties may have significant implications for their use in homogeneous catalysis. In the present report, half-sandwich Ir-Cp* complexes of two different azocarboxamide ligands are presented. Different coordination motifs of the ligand were realized using base and chloride abstracting ligand to give N boolean AND N-, N boolean AND O-, and N boolean AND C-chelated monomeric iridium complexes. For the azocarboxamide ligand having methoxy substituted at the phenyl ring, a mixture of N boolean AND C-chelated mononuclear (Ir-5) and N boolean AND N,N boolean AND C-chelated dinuclear complexes (Ir-4) were obtained by activating the C-H bond of the aryl ring. No such C-H activation was observed for the ligand without the methoxy substituent. The molecular identity of the complexes was confirmed by spectroscopic analyses, while X-ray diffraction analyses further confirmed three-legged piano-stool structure of the complexes along with the above binding modes. All complexes were found to exhibit remarkable activity as precatalysts for the transfer hydrogenation of carbonyl groups in the presence of a base, even at low catalyst loading. Optimization of reaction conditions divulged superior catalytic activity of Ir-3 and Ir-4 complexes in transfer hydrogenation over the other catalysts. Investigation of the influence of binding modes on the catalytic activity along with wide range substrates, tolerance to functional groups, and mechanistic insights into the reaction pathway are also presented. These are the first examples of C-H activation in azocarboxamide ligands.